Coumarins in the tumor-immune application: from molecular mechanisms to therapeutic innovations - Zhao, Yufan; Jing, Lingjie; Han, Leng; Guo, Cheng; Yang, Quanjun (Frontiers in Immunology, 2025)
Coumarin compounds represent a class of natural or synthetic molecules characterized by a benzo-α-pyrone skeleton. Their diverse substituents and extensive biological activities have garnered significant attention in the fields of anti-tumor therapy and immune regulation in recent years. This article systematically reviews the mechanisms by which coumarins influence tumor immunity. Coumarins directly inhibit tumor progression by inducing apoptosis in tumor cells, inhibiting cellular proliferation, and blocking epithelial-mesenchymal transition (EMT) and angiogenesis. However, they reshape the tumor microenvironment (TME) by regulating platelet function, macrophage polarization, T cell activity, NK cell cytotoxicity, and cytokine networks, thereby enhancing the host’s anti-tumor immune response. Despite the promising potential of coumarins in tumor immunotherapy, their mechanisms are complex, their clinical translation remains limited, and safety concerns warrant further investigation. This review summarizes the research progress on coumarins, discusses the challenges and future directions for their development, and aims to provide a comprehensive reference for the mechanism analysis and translational applications of coumarins in tumor immunotherapy. Furthermore, it seeks to facilitate the development of innovative drugs derived from natural products and to promote their clinical translation.